Adaptation of Agile Project Management to Small Scale Projects in the Indonesian MSME Sector - Loso Judijanto; Dwi Kartika Prananingrum; Arief Yanto Rukmana; Mei Rani Amalia; Siera Syailendra; Gustian Djuanda (Eastasouth Institute, 2025)
Agile Project Management (APM) offers a flexible and adaptive approach to managing projects, making it particularly relevant for the dynamic environment of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. This study explores the adaptation of APM for small-scale projects within the MSME sector through qualitative analysis. Data were collected from five informants actively involved in project management and analyzed using N-VIVO software. The findings highlight that APM can enhance adaptability, team collaboration, and customer satisfaction. However, challenges such as limited resources, resistance to change, and lack of expertise were identified. Strategies, including incremental adoption, training, and external consultancy, were proposed to overcome these barriers. This research contributes to the understanding of Agile's applicability in MSMEs, offering practical insights for practitioners and policymakers to foster innovation and competitiveness in the sector.